Are Corporate General Counsels in Top Management Effective Monitors? Evidence from Stock Price Crash Risk. Issue 2 (15th March 2021) - Al Mamun, MD; Balachandran, Balasingham; Duong, Huu Nhan; Gul, Ferdinand A
Abstract: We find that firms with a top management counsel ( TMC ) have lower stock price crash risk than other firms. We further show that firms with a TMC issue more negative relative to positive earnings guidance and use more negative relative to positive words in their annual report filings, compared to firms without a TMC . TMC s are more effective in mitigating crash risk when they serve on the board. Our findings support the monitoring role of TMC s in mitigating bad news hoarding, which, in turn, contributes to the reduction in crash risk.